Studi Kasus di DPRD Kota Padang Panjang Mengenai Proses Pembuatan Peraturan Daerah di Bidang Pendidikan - Naila Zulfa (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The purpose of this study was to find out about the concept and procedure for making legislative products of Regional Regulations in the field of education of the Padang Panjang City DPRD which include: 1) the concept of regional regulations in the field of education in general in Padang Panjang City, 2) the reasons for the formation of Regional Regulations on education in general and specifically in Padang Panjang City, 3) interested parties in making Regional Regulations on education in Padang Panjang City, 4) types of Regional Regulations on education in general and specifically in Padang Panjang City, 5) the process of making Regional Regulations on education in Padang Panjang City. This study uses a descriptive qualitative method. The research findings and conclusions are, the concept and procedure for making education regulations in Padang Panjang city are legal products issued by the local government (DPRD together with the regional head) to regulate the implementation of education at the regional level. The process of making education regulations in Padang Panjang is through identifying problems that are trending in society, then the Padang Panjang DPRD absorbs people's aspirations by going directly to the field to hear the hopes of the community, after that the preparation of the Academic Manuscript involves a team of experts and experts from the field of education, conducting public consultations, discussions in the DPRD through several stages, then the education regulation is tested and monitored and if it has a good impact it will be socialized, ratified by the mayor to be determined and implemented by the community. In making these education regulations, of course, it is necessary to involve various stakeholders such as the local government, education office, community and academics so that the regulations made are right on target and have a good impact on education in the area.